2019
DOI: 10.1200/jco.2019.37.15_suppl.3085
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human study of AZD5153, a small molecule inhibitor of bromodomain protein 4 (BRD4), in patients (pts) with relapsed/refractory (RR) malignant solid tumor and lymphoma: Preliminary data.

Abstract: 3085 Background: BRD4 is a bromodomain and extraterminal (BET) protein that regulates oncogenic programs by modifying gene transcription and additional mechanisms. AZD5153 is a novel, reversible BRD4 inhibitor with bivalent mechanism of action and enhanced antitumor activity in preclinical models. This phase 1, multicenter, dose escalation study (NCT03205176) assesses AZD5153’s safety, pharmacokinetics (PK), and pharmacodynamics (PD). We report here preliminary, unvalidated data from AZD5153 monotherapy in pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…28 Thus, BET inhibitors, like AZD5153 and GSK525762, could be promising candidates for further clinical usage in Myc-deregulated cancer. 29 Besides, a strategy or technology termed as proteolysis targeting chimera (PROTAC) has been developed recently to hijack the Cereblon E3 ubiquitin ligase for degrading specific oncoproteins, such as BRD4, potently and constantly. 30 PROTAC was first used as a chemical knock-down approach with reversibility and has been recently explored to satisfy additional needs, including drug discovery.…”
Section: Alternative Methods To Target Mycmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Thus, BET inhibitors, like AZD5153 and GSK525762, could be promising candidates for further clinical usage in Myc-deregulated cancer. 29 Besides, a strategy or technology termed as proteolysis targeting chimera (PROTAC) has been developed recently to hijack the Cereblon E3 ubiquitin ligase for degrading specific oncoproteins, such as BRD4, potently and constantly. 30 PROTAC was first used as a chemical knock-down approach with reversibility and has been recently explored to satisfy additional needs, including drug discovery.…”
Section: Alternative Methods To Target Mycmentioning
confidence: 99%
“… 28 Thus, BET inhibitors, like AZD5153 and GSK525762, could be promising candidates for further clinical usage in Myc-deregulated cancer. 29 …”
Section: Alternative Methods To Target Mycmentioning
confidence: 99%
“…In addition, this combo was relatively well-tolerated, likely because the adverse effects of mTORi and BETi affect different organ systems. In contrast, the AKTi and BETi combo had poor tolerability in vivo despite being synergistic in vitro, probably because of overlapping adverse effects (e.g., diarrhea) of AKTi and BETi (42,43). These results stress the need to select the drugs with non-overlapping toxicities to increase antitumor activity and minimize adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, AZD5153 demonstrated a cytotoxic effect at a concentration 100 nM and tumour regression at concentrations 2.5-10 mg/kg for AML and prostate cancer xenografted tumours [57][58][59]. AZD5153 progressed to clinical trial, which reported similar DLTs as for OTX015, indicating that although BETis' chemical structure is diverse, toxicities may be shared across BETis [60]. A dose escalation study of a new BETi, BAY1238097, in eight patients with solid cancers was prematurely terminated due to DLTs [61].…”
Section: Bet Inhibitors In Clinical Trialsmentioning
confidence: 99%